GENESIS OF THE INSTITUTE FOR JUDICIAL DECISION REVISION IN CRIMINAL PROCEEDINGS - Sadriddinova Latofat (Scholar Express Journals, 2024)
This article provides explanations on the role of judicial bodies in the system of state power in criminal justice, legal status, proceedings in criminal courts, the content and essence of the courts of first, appeal, Cassation, their activities, powers, reforms implemented and implemented in the judicial system.
Keywords: The genesis of the institution of review; court decisions in criminal proceedings; appeal courts